THE CONCEPT AND CHARACTERISTICS OF THE NECESSARY DEFENSE (World Bulletin of Management and Law, 2022)
This scientific article discusses the concept and characteristics of the necessary defense. In addition, there is a subjective and objective side to the study of the necessary defense, and appropriate recommendations have been developed based on the analysis of the results of scientific research
Keywords: Concept; characteristic; necessary defense; criminal law